How much are multisectoral programs worth? A new method with an application to school meals - Alderman, Harold; Aurino, Elisabetta; Baffour, Priscilla Twumasi; Gelli, Aulo; Turkson, Festus; Wong, Brad (International Food Policy Research Institute, 2021)
Social protection programs such as cash or food transfers support current poverty and inequality reduction goals, while at the same time enhance future productivity through human capital investments. Yet, the quantification of their overall productivity and equity benefits is challenging. We address this question utilizing a new methodology that quantifies productivity gains from learning as well as an approach for assessing social protection benefits. We do so by combining data on distributional benefits stemming from current poverty reduction in conjunction with future human capital gains in the context of a large-scale national school feeding program in Ghana. We develop a straightforward approach to map effect sizes from randomized controlled studies into broader economic analyses. In addition, we include the often recognized, but seldom quantified, distributional impacts of multi-sectoral investments. Our methodology is relevant to a broad range of social protection programs that have multidimensional benefits spanning both human capital improvements and equity gains.